RiPKI: The Tragic Story of RPKI Deployment in the Web Ecosystem - Matthias Wählisch and Robert Schmidt and Thomas C. Schmidt and Olaf Maennel and Steve Uhlig and Gareth Tyson (Association for Computing Machinery (ACM), 2015)
Web content delivery is one of the most important services on the Internet. Access to websites is typically secured via TLS. However, this security model does not account for prefix hijacking on the network layer, which may lead to traffic blackholing or transparent interception. Thus, to achieve comprehensive security and service availability, additional protective mechanisms are necessary such as the RPKI, a recently deployed Resource Public Key Infrastructure to prevent hijacking of traffic by networks. This paper argues two positions. First, that modern web hosting practices make route protection challenging due to the propensity to spread servers across many different networks, often with unpredictable client redirection strategies; and, second, that we need a better understanding why protection mechanisms are not deployed. To initiate this, we empirically explore the relationship between web hosting infrastructure and RPKI deployment. Perversely, we find that less popular websites are more likely to be secured than the prominent sites. Worryingly, we find many large-scale CDNs do not support RPKI, thus making their customers vulnerable. This leads us to explore business reasons why operators are hesitant to deploy RPKI, which may help to guide future research on improving Internet security.
Keywords: BGP; RPKI; secure inter-domain routing; deployment; hosting infrastructure; CDN